The establishment of the national key ecological functional zone and the county’s ecological green development - Rong-bo, Zhang; Chang-biao, Zhong (Frontiers in Ecology and Evolution, 2023)
Based on the literature review and theoretical mechanism, this paper selects 1997 county-level data indicators in mainland China from 2007 to 2019 to explore the role of the establishment of national key ecological function areas on the ecological green development of counties. The implementation of the national key ecological function zone policy can significantly increase the vegetation normalization index by about 0.035-0.037 units. The implementation of the policy has greatly increased the biomass density in the county, and expanded the capacity and range of above-ground and below-ground biomass. The reduction of large-scale investment by the government, the improvement of quality and efficiency of enterprises in the region, and the increase in the area of artificial afforestation are important transmission mechanisms for the implementation of policies to affect the green development of counties. The implementation of the policy has a positive green spillover effect on adjacent areas, which can realize regional coordinated ecological governance. Each additional hectare of artificial afforestation can absorb about 134,800 tons of carbon emissions each year, bringing an additional income of 730 million yuan. It releases about 98,000 tons of oxygen a year, which can be used for 1.312 billion people for oxygen respiration consumption every year.